Clinical management and outcome of pregnancies complicated by cerebral venous thrombosis: a review of 19 cases - Demir, C. F.; Yildiz, M.; Ozdemir, H. H.; Inci, F.; Erdogan, E. (Wiley-Blackwell, 2012)
[Abstract Not Available]
16th Congress of the European-Federation-of-Neurological-Societies (EFNS) -- SEP 08-11, 2012 -- Stockholm, SWEDEN